Knowledge, Attitude and Practice of Adverse Drug Reactions Reporting among Health Care Workers at Devdaha Medical College and Research Institute, Bhaluhi, Rupandehi - Guragain, Sanjeev; Upadhaya, Namrata (Medical Journal of Eastern Nepal, 2024)
Background: Adverse drug reactions (ADRs) are unintended and noxious responses of a drug when used at normal doses in human beings. Increased incidence of ADRs is the challenge for the health care workers (HCWs) throughout the world. Therefore, we focused to assess the knowledge, attitude and practice of ADRs among HCWs at tertiary care hospital, Devdaha. Methods: This study is a cross-sectional questionnaire based descriptive study. The validated questionnaire consists of questions that contains scores to categorize knowledge and attitude among HCWs. It also documented practice adopted by the HCWs at the hospital. Out of 50 HCWs approached, 26 gave consent to participate in the study. The collected data were entered in excel and expressed in percentage or frequency. Results: All HCWs, 26 (100%), have heard about pharmacovigilance. However, only 11 (42.31%) participants have adequate knowledge regarding ADRs. In which, 22 (84.62%) expressed desire to report ADRs that they encounter during their medical practice. But, they have not reported any ADRs till date. Moreover, only 12 (46.15%) participants have positive attitude towards ADRs reporting. In case of practice, nine (34.62%) participants mentioned that the main factor that hinders them to practice reporting of ADRs is unavailability of the ADRs reporting form in the institute. Almost all (21) HCWs wanted training in pharmacovigilance. Conclusion: All HCWs are fully aware of ADRs but most of them show inadequate knowledge regarding ADRs. Over half of them lack positive attitude towards ADRs reporting and the practice of ADRs reporting is not satisfactory. Further, proper training of pharmacovigilance and form to report ADRs reporting should be provided in the hospital.